Faktor-Faktor yang Mempengaruhi Kepuasan Kerja Karyawan (Studi pada Karyawan Bagian Marketing PT. Indosat, Tbk Semarang) - Untarji, Yohanes Doni; ., Suhaji (Jurnal Kajian Akuntansi dan Bisnis, 2012)
The aim of this research was to find out the influence of individual factor,social factor and primary factor of work towards job satisfaction at PT IndosatSemarang. The population in this research was the entire employees, they were 110employees at PT Indosat Semarang. The samples were 52 respondents. The techniquesampling used in this research was purposive sampling judgement. The analysis tool usedin this research was multiple linear regression, which was firstly examined by validityand reliabilities test. The research result showed that the individual factor influenced theemployeeâs job satisfaction at PT Indosat Semarang, the social factor influenced theemployeeâs job satisfaction at PT Indosat Semarang. The primary factor influenced jobsatisfaction at PT Indosat Semarang. The individual factor, social factor and primaryfactor of work simultaneously influenced employeeâs job satisfaction at PT IndosatSemarang.Keywords : Individual factor, social factor and primary factor of work towards work jobsatisfaction